2002
DOI: 10.1007/s12126-002-1014-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in new partnership choices and constraints for older widows and widowers

Abstract: There is an 'urban myth,' nevertheless widely held, that in widowhood, women grieve and men replace. Indeed, demographic data indicate that older widowed men are more likely to remarry than older widowed women. This article reports a small-scale study of twenty-five widows and twenty-six widowers over the age of sixty-five in the UK. The study focuses on the choices and constraints in the making of new dyadic relationships and how men and women differ in their approaches to them. What emerges from the intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 13 publications
4
75
0
1
Order By: Relevance
“…Stressful family relationships can create tension in the new postbereavement marriage. Researchers have found that remarriage creates stress for widows and widowers who worry that their children and other family members disapprove of their marriage (Davidson, 2002;Moore & Stratton, 2001;van den Hoonaard, 2010). Further, research might even suggest that those who begin dating soon after a loss might experience strained relationships with their children (van den Hoonaard, 2010).…”
Section: Results In the Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Stressful family relationships can create tension in the new postbereavement marriage. Researchers have found that remarriage creates stress for widows and widowers who worry that their children and other family members disapprove of their marriage (Davidson, 2002;Moore & Stratton, 2001;van den Hoonaard, 2010). Further, research might even suggest that those who begin dating soon after a loss might experience strained relationships with their children (van den Hoonaard, 2010).…”
Section: Results In the Existing Literaturementioning
confidence: 99%
“…After experiencing a major loss, most adults instinctively look for support from other caring adults within their network (Anderson & Greene, 2013). This dilemma is enhanced by the fact that when seeking support, unique gender differences can exist, with men commonly seeking out new relationships to dispel loneliness (Baum, 2003;Davidson, 2002). Whereas some women might fear the impending responsibility of caring for another adult, and therefore avoid future relationships, others might seek a relationship for financial stability (Anderson & Greene, 2013;Ganong & Coleman, 2004).…”
Section: Implications For Marital and Family Therapistsmentioning
confidence: 99%
“…The available research on dating tends to focus on the experiences of adolescents and young adults (Dickson et al, 2005; McElhany, 1992). Research regarding dating in later life explores factors associated with the likelihood to date (Bulcroft & Bulcroft, 1991), the desire to date (Calasanti & Kiecolt, 2007; Davidson, 2002; Dickson et al, 2005; Stevens, 2002), the reasons to date (Bulcroft & O’Conner, 1986; Calasanti & Kiecolt, 2007; Cooney & Dunne, 2001; Dickson et al, 2005), and the impact of dating relationships on health and well-being (Bulcroft & Bulcroft, 1991; Bulcroft & O’Conner, 1986; Carr, 2004). …”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Living apart together (LAT) relationships, where partners maintain separate households and finances, are becoming more common in northern and western Europe (Davidson 2002;De Jong Gierveld 2004;Karlsson and Borell 2002;Castro-Martín et al 2008). This type of partnership is prevalent also at older ages and is a preliminary stage of the courtship process potentially leading to cohabitation.…”
Section: Household Position and Adult Healthmentioning
confidence: 99%